Late-stage difluoromethylation: concepts, developments and perspective. (2nd June 2021) - Sap, Jeroen B. I.; Meyer, Claudio F.; Straathof, Natan J. W.; Iwumene, Ndidi; am Ende, Christopher W.; Trabanco, Andrés A.; Gouverneur, Véronique
Abstract : This review describes the conceptual advances that have led to the multiple difluoromethylation processes making use of well-defined CF2 H sources. Abstract : This review describes the recent advances made in difluoromethylation processes based on X–CF2 H bond formation where X is C(sp), C(sp 2 ), C(sp 3 ), O, N or S, a field of research that has benefited from the invention of multiple difluoromethylation reagents. The last decade has witnessed an upsurge of metal-based methods that can transfer CF2 H to C(sp 2 ) sites both in stoichiometric and catalytic mode. Difluoromethylation of C(sp 2 )–H bond has also been accomplished through Minisci-type radical chemistry, a strategy best applied to heteroaromatics. Examples of electrophilic, nucleophilic, radical and cross-coupling methods have appeared to construct C(sp 3 )–CF2 H bonds, but cases of stereoselective difluoromethylation are still limited. In this sub-field, an exciting departure is the precise site-selective installation of CF2 H onto large biomolecules such as proteins. The formation of X–CF2 H bond where X is oxygen, nitrogen or sulfur is conventionally achieved upon reaction with ClCF2 H; more recently, numerous protocols have achieved X–H insertion with novel non-ozone depleting difluorocarbene reagents. All together, these advances have streamlined access to molecules of pharmaceutical relevance, and generated interest for process chemistry.